Peran Sentral Pengembangan Sumber Daya Manusia Aparatur melalui Meritokrasi - Aminuddin, Aminuddin; Rindaningsih, Ida (Al-DYAS, 2025)
The legal provisions that regulate the management of Civil Servants through the merit system need to be considered for their role in human resource management within the bureaucracy. Therefore, it is important to understand the role of human resource development for civil servants as a driving force in the machinery of government bureaucracy. This research employs a qualitative research method with a desk research approach, utilizing secondary data sources. The findings of the study indicate that through meritocracy, Civil Servants have the opportunity to develop themselves, protect their careers from political influence, and enhance motivation through fair recognition. Additionally, the merit system provides a clear career path, facilitates professional recruitment, and ensures efficient filling of positions. In conclusion, this will contribute to improving the quality of life for the community and creating a government that is more effective, efficient, and free from practices of corruption, collusion, and nepotism.